Design of Ag nanograting for broadband absorption enhancement in amorphous silicon thin film solar cells. (November 2015) - Liu, Ping; Yang, Shi-e; Ma, Yanxia; Lu, Xiangyang; Jia, Yukun; Ding, Dong; Chen, Yongsheng
Abstract: Light trapping is one of the key issues to improve the light absorption and increase the efficiency of thin film solar cells. The effects of the triangular Ag nanograting on the absorption of amorphous silicon solar cells were investigated by a numerical simulation based on the finite element method. The light absorption under different angle and area of the grating has been calculated. Furthermore, the light absorption with different incident angle has been calculated. The optimization results show that the absorption of the solar cell with triangular Ag nanograting structure and anti-reflection film is enhanced up to 96% under AM1.5 illumination in the 300–800 nm wavelength range compared with the reference cell. The physical mechanisms of absorption enhancement in different wavelength range have been discussed. Furthermore, the solar cell with the Ag nanograting is much less sensitive to the angle of incident light. These results are promising for the design of amorphous silicon thin film solar cells with enhanced performance.